Economic Perspectives on the Income Taxation of Couples and the Choice of Tax Unit - Rees, Ray (Berlin, 2017)
This paper examines the case for replacing joint income by individual income as the base for the taxation of two-earner families. It draws upon well-established economic theory to support the argument. This shows that individual taxation is superior to joint taxation (“income-splitting”) on grounds of both efficiency and equity. It also briefly reports on important recent empirical work that shows that in Germany moving from joint to individual taxation while at the same time increasing the availability of affordable pre-school child care would be self-financing and have a positive net social benefit.
A Review of the Literature
Keywords: Einkommen; Familie; 343 Wehrrecht, Steuerrecht, Wirtschaftsrecht; Steuer